Valorization of Palm Oil Fuel Ash for Sustainable Partial Cement Replacement in Concrete: A Mini Review - Boateng, Kwame Mensah; Owusu, Abena Serwaa; Mohd Yazid, Siti Farhana; Puspitasari, Surya Dewi; Wijayanti, Yureana (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Palm Oil Fuel Ash (POFA), a by-product from the combustion of palm oil mill residues, has emerged as a highly promising supplementary cementitious material (SCM) to enhance sustainability in the construction industry. This paper reviews the physical and chemical characteristics, mechanical performance, optimal replacement levels, and the associated economic and environmental implications of incorporating POFA in concrete. Physically, POFA is characterized by its low specific gravity, initially coarse particle size, and porous structure, which can be refined through grinding to achieve finer particles with increased surface area and improved pozzolanic reactivity. Chemically, POFA is rich in silicon dioxide (SiO₂), with appreciable amounts of aluminium trioxide (Al₂O₃) and ferric oxide (Fe₂O₃), meeting the ASTM International C618-12 requirements for Class F pozzolans. These characteristics enable POFA to react with calcium hydroxide produced during Ordinary Portland Cement (OPC) hydration, forming additional calcium silicate hydrate (C-S-H) gel, thereby enhancing strength and durability. Experimental studies have demonstrated that partial replacement of OPC with finely ground POFA, particularly at levels between 10–30%, can improve long-term compressive strength, reduce permeability, and enhance resistance to chloride penetration and sulphate attack. Economically, incorporating POFA reduces dependence on energy-intensive OPC, resulting in lower production costs, while environmentally, it minimizes landfill waste, decreases greenhouse gas emissions, and promotes circular economy practices. In palm oil-producing nations such as Malaysia and Indonesia, utilizing POFA in concrete can simultaneously address the challenges of industrial waste management and cement industry decarbonization, offering a viable pathway towards sustainable construction.